If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -1x)(3x + 6) = 0 Reorder the terms: (5 + -1x)(6 + 3x) = 0 Multiply (5 + -1x) * (6 + 3x) (5(6 + 3x) + -1x * (6 + 3x)) = 0 ((6 * 5 + 3x * 5) + -1x * (6 + 3x)) = 0 ((30 + 15x) + -1x * (6 + 3x)) = 0 (30 + 15x + (6 * -1x + 3x * -1x)) = 0 (30 + 15x + (-6x + -3x2)) = 0 Combine like terms: 15x + -6x = 9x (30 + 9x + -3x2) = 0 Solving 30 + 9x + -3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(10 + 3x + -1x2) = 0 Factor a trinomial. 3((5 + -1x)(2 + x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {5, -2}
| 12x^3=15 | | 114-4x=14x+16 | | 83-5x=31x+23 | | 7x-x^2=11 | | 4x*-15x-4=0 | | 59-2x=16x+21 | | -6(-1)-2= | | -y-6y= | | -x^3+7x^2-11x=0 | | -135-7x=10x | | 12x-34=5x+2 | | 3x-x^2-5=0 | | 5x^8-4x^6-2x^4-4x^2+1=0 | | (n+2)*2=8 | | (n-5)*2=6 | | (n+1)*8=24 | | x^3+2*x^2-19x=0 | | 4-2y+3=-9 | | x^4-3x-4=0 | | 200+3=1800 | | 3*4x-6x=2*9x | | 40t=55+3t | | x-(x-0.2x)=43.46 | | -x^3+5x^2+10x-50=0 | | 12=4x-x | | 2(x-1)=3/5(10+5x) | | 63x^7=7x^5 | | y=-4(2)+5 | | y=-4(1)+5 | | (8x-12)(10-15x)=0 | | y=-4(0)+5 | | y=-4(-1)+5 |